2008
DOI: 10.1590/s1413-70542008000100037
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de proteína bruta e de energia metabolizável para frangas de postura semipesadas de 1 a 18 semanas de idade

Abstract: Objetivou-se neste experimento avaliar o desempenho de poedeiras comerciais de 1 a 18 semanas de idade submetidas a níveis de Proteína Bruta (PB) e de Energia Metabolizável (EM). O experimento foi desenvolvido no aviário de Departamento de Zootecnia do Centro de Ciências Agrárias da UFPB, em Areia-PB. Foram utilizadas 432 pintainhas Lohmann Brown de três dias de idade, distribuídas em um delineamento inteiramente casualizado, em esquema Fatorial 3x3, com três níveis de PB e três níveis de EM. Na primeira fase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It is suggested that digestible lysine levels in the grower feed did not restore body weight in underweight hens; however, protein levels in the experimental feeds was 14 (g/kg), which may have been low and therefore compromised protein synthesis for weight recovery, as crude protein levels in feed can influence weight gain (BARROS et al, 2006). Neto et al, (2008) verified that Lohmann Brown layers showed greater weight gain when fed grower feed (13 to 18 weeks) with 16% crude protein.…”
Section: Resultsmentioning
confidence: 69%
“…It is suggested that digestible lysine levels in the grower feed did not restore body weight in underweight hens; however, protein levels in the experimental feeds was 14 (g/kg), which may have been low and therefore compromised protein synthesis for weight recovery, as crude protein levels in feed can influence weight gain (BARROS et al, 2006). Neto et al, (2008) verified that Lohmann Brown layers showed greater weight gain when fed grower feed (13 to 18 weeks) with 16% crude protein.…”
Section: Resultsmentioning
confidence: 69%